R‐COMP versus R‐CHOP as first‐line therapy for diffuse large B‐cell lymphoma in patients ≥60 years: Results of a randomized phase 2 study from the Spanish GELTAMO group - Juan‐Manuel Sancho; Rubén Fernández‐Alvarez; Francisco Gual‐Capllonch; Esther González‐García; Carlos Grande; Norma Gutiérrez; María‐Jesús Peñarrubia; Ana Batlle‐López; Eva González‐Barca; José‐María Guinea; Eva Gimeno; Francisco‐Javier Peñalver; et al. (Cancer Medicine, 2021)
Abstract The use of non‐pegylated liposomal doxorubicin (Myocet®) in diffuse large B‐cell lymphoma (DLBCL) has been investigated in retrospective and single‐arm prospective studies. This was a prospective phase 2 trial of DLBCL patients ≥60 years old with left ventricular ejection fraction (LVEF) ≥55% randomized to standard R‐CHOP or investigational R‐COMP (with Myocet® instead of conventional doxorubicin). The primary end point was to evaluate the differences in subclinical cardiotoxicity, defined as decrease in LVEF to <55% at the end of treatment. Secondary objectives were efficacy, safety, and variations of troponin and N‐terminal pro‐B‐type natriuretic peptide (NT‐proBNP) and LVEF along follow‐up. Ninety patients were included, 45 in each group. No differences were observed in the percentage of patients with LVEF <55% at end of treatment (11% in R‐CHOP arm vs. 7% in R‐COMP arm, p = 0.697) or at 4 months (10% vs. 6%, respectively, p = 0.667) and 12 months (8% vs. 7%, respectively, p = 1). However, a higher percentage of R‐CHOP compared with R‐COMP patients showed increased troponin levels in cycle 6 (100% vs. 63%, p = 0.001) and at 1 month after treatment (88% vs. 56%, respectively, p = 0.015). Cardiovascular adverse events were seen in five R‐CHOP patients (nine episodes, four grade ≥3) and in four R‐COMP patients (five episodes, all grade 1–2). No significant differences in efficacy were observed. In conclusion, R‐COMP is a feasible immunochemotherapy schedule for DLBCL patients ≥60 years, with similar efficacy to R‐CHOP. However, the use of non‐pegylated doxorubicin instead of conventional doxorubicin was not associated with less early cardiotoxicity, although some reduced cardiac safety signals were observed. Trial registration: ClinicalTrials.gov Identifier: NCT02012088.